Machine Learning and Experimental Validation Identified Ferroptosis Signature and Innovative Biomarkers (ESR1 and GSTZ1) in Liver Fibrosis - Luo W; Wu H; Yang Z; Lan T; Wu L; Huang Y (Journal of Inflammation Research)
Wen Luo,1 Hongwen Wu,2 Zhijie Yang,2 Tian Lan,2 Liya Wu,3 Yushen Huang2 1Department of Gastrointestinal Surgery, Liuzhou Workers Hospital, Liuzhou, People’s Republic of China; 2Department of Pharmacy, Liuzhou Workers Hospital, Liuzhou, People’s Republic of China; 3Department of Neurology, Liuzhou Workers Hospital, Liuzhou, People’s Republic of ChinaCorrespondence: Yushen Huang; Liya Wu, Email hys@sr.gxmu.edu.cn; wly31742858@126.comBackground: Targeting ferroptosis is an effective approach to mitigate hepatic fibrosis, yet no reports exist on the ferroptosis signature in liver fibrosis. This study aimed to explore ferroptosis characteristics in this disease.Methods: RNAseq data from GSE6764, GSE188604 and Cancer Genome Atlas Liver Hepatocellular Carcinoma (TCGA-LIHC) were downloaded. Multiple machine learning methods, including Weighted Gene Co-expression Network Analysis (WGCNA), Random Forest (RF) and Support Vector Machine (SVM), were used to identify core genes in liver fibrosis and ferroptosis. WGCNA can pinpoint modules linked to clinical traits, aiding in discovering diagnostic and progression molecules in complex diseases. RF and SVM are often utilized for WGCNA validation to boost result accuracy. Carbon tetrachloride (CCl4) was used to establish a mouse liver fibrosis model to validate core gene expression, which was also assessed in test and validation GEO datasets. Finally, the diagnostic role of the core genes in liver fibrosis and hepatocellular carcinoma (HCC) was also investigated using ROC analysis.Results: Multiple machine learning methods screened nine core genes, including IL1B, GSTZ1, LIFR, SLC25A37, PTGS2, MT1G, HSPB1, ESR1, and PHGDH. In vivo experimental validation, RT-PCR showed ESR1 and GSTZ1 were significantly under-expressed in the liver fibrosis group compared to the normal group. Simultaneously, in GSE6764 and GSE188604, ESR1 and GSTZ1 were also identified as protective genes for liver fibrosis. More in-depth research found that ESR1 and GSTZ1 exhibited a good diagnostic performance both in liver fibrosis and HCC, suggesting that a persistent decrease in ESR1 and GSTZ1 in patients might signal the progression from hepatic fibrosis to HCC.Conclusion: The present study is the first to report the ferroptosis signature in liver fibrosis and identifies two novel biomarkers, ESR1 and GSTZ1, providing new insights for the diagnosis and treatment of liver fibrosis in the future.Keywords: ESR1, GSTZ1, ferroptosis, liver fibrosis, biomarker